2013
DOI: 10.1007/s40273-013-0111-0
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Cost Effectiveness of Pre-Exposure Prophylaxis for HIV Prevention in the US

Abstract: About 50,000 people are infected with HIV in the US each year and this number has remained virtually the same for the past decade. Yet, in the last few years, evidence from several multinational randomized clinical trials has shown that the provision of antiretroviral drug to uninfected persons (i.e. pre-exposure prophylaxis) reduces the incidence of HIV by about 50 %. However, evidence from cost-effectiveness studies conducted in the US yield widely varying estimates of the cost per quality-adjusted life-year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Drug costs will be a major determinant with Truvada costing as much as $10,000 per year in some countries. 58 Additionally, local variation in HIV, condom use and patterns of sex work may dramatically affect the effectiveness of microbicides 59 and oral PrEP. 60 …”
Section: Costing a New Responsementioning
confidence: 99%
“…Drug costs will be a major determinant with Truvada costing as much as $10,000 per year in some countries. 58 Additionally, local variation in HIV, condom use and patterns of sex work may dramatically affect the effectiveness of microbicides 59 and oral PrEP. 60 …”
Section: Costing a New Responsementioning
confidence: 99%
“…A number of literature reviews on the cost-effectiveness of PrEP have been performed: some specific to the US (22) and some more general (23). A previous literature review of cost-effectiveness studies in the US (all in MSM), concluded that there was substantial variation in the cost per QALY gained.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, a French study found additional benefits associated with the introduction of PrEP, such as the treatment of other diseases and a reduction in secondary infections [ 141 ]. In sum, even though the cost-effectiveness results vary, it appears that PrEP can be a cost-effective addition to other HIV prevention programmes since it has the potential to prevent a substantial number of HIV infections and thus to mitigate the HIV epidemic [ 142 ]. Existing evidence suggests that the enormous upfront costs in providing PrEP should result in substantial economic benefits in the long term [ 143 ].…”
Section: Methodsmentioning
confidence: 99%